2017
DOI: 10.1089/ars.2016.6650
|View full text |Cite
|
Sign up to set email alerts
|

Graded Response of the Multifunctional 2-Cysteine Peroxiredoxin, CgPrx, to Increasing Levels of Hydrogen Peroxide in Corynebacterium glutamicum

Abstract: These results reveal that CgPrx functions as a multifunctional protein crucial for adapting appropriate responses to different levels of oxidative challenge in C. glutamicum. Antioxid. Redox Signal. 26, 1-14.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 51 publications
2
34
1
Order By: Relevance
“…However, no significant changes in the expression of these genes were observed in the H 2 O 2 subgroup. This effect may be attributed to H 2 O 2 treatment exceeding the working range for peroxiredoxins (Bang et al, 2016;Si et al, 2017). In addition, intracellular ROS tests showed that light reduced the intracellular ROS level in magnetic cells, suggesting that light can reduce the oxidative stress level in these cells.…”
Section: Discussionmentioning
confidence: 98%
“…However, no significant changes in the expression of these genes were observed in the H 2 O 2 subgroup. This effect may be attributed to H 2 O 2 treatment exceeding the working range for peroxiredoxins (Bang et al, 2016;Si et al, 2017). In addition, intracellular ROS tests showed that light reduced the intracellular ROS level in magnetic cells, suggesting that light can reduce the oxidative stress level in these cells.…”
Section: Discussionmentioning
confidence: 98%
“…In C . glutamicum , the major targets for S -mycothiolation are the maltodextrin phosphorylase MalP and the thiol-peroxidase Tpx and it was shown that S -mycothiolation inhibited the activities of MalP and Tpx 10, 15 . Thus, it seems that abundant redox-sensitive metabolic enzymes are the main targets for inactivation by S -thiolations in different bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The redox-regulatory mechanisms of S -mycothiolated proteins have been studied thus far for several antioxidant enzymes, such as thiol peroxidases (Tpx, Mpx, AhpE) and methionine sulfoxide reductases (MsrA) 10, 1215 . Moreover, Tpx has been shown to function as a peroxidase and as oligomeric chaperone in response to different levels of H 2 O 2 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…al . reported that an atypical 2-Cys Prx in C. glutamicum mainly exists as a monomer and displays a Trx-dependent peroxidase activity at low peroxide concentrations; over oxidation induces Prx sulfonation irreversibly inactivates its peroxidase activity, and in turn, activates its oligomerization and chaperone activities [33]. Thus, the yin and yang relationship of the peroxidase and chaperone activities of Prx is crucial for maintaining protein homeostasis in cells.…”
Section: Discussionmentioning
confidence: 99%